Isolation and identification of bacterial pathogens from cloacal swabs of turkeys and their antimicrobial sensitivity patterns - Roy, Polash Chandra; Hossain, Md Khaled; Rumi, Nazmi Ara; Rahman, Md Shajedur; Mahmud, Md Shahin; Hossion, Ishaq (Asian Journal of Medical and Biological Research, 2018)
The present study was carried for the isolation, identification of bacterial pathogens from cloacal swabs of turkeys during the period from January-June, 2016. The entire research work was conducted in the Department of Microbiology, Faculty of Veterinary and Animal Science, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur. The study was performed with 48 cloacal swab samples. The cloacal swab samples were collected carefully from three different Turkey Farms randomly and transferred aseptically to the laboratory. On the basis of morphology, staining, cultural and biochemical characteristics it was found that among the isolates 25(52.08%) samples were positive E. coli, 10(20.83%) samples were positive for Salmonella spp., 9(18.76%) samples were positive for both E. coli and Salmonella spp. and 4(8.33%) samples shown no growth in subculture media. Antibiogram profiles indicate that E. coli isolated were 100% sensitive to Azithromycin, Kanamycin and Ciprofloxacin, 80% sensitive to Cefradine, Vancomycin and Levofloxacin, 60% sensitive to Cefotetan and Nitrofurantoin and 40% sensitive to Erythromycin. The isolates were 100% resistant to Cloxacillin and Cefixime. On the other hand, Salmonella spp. were 100% sensitive to Azithromycin, Kanamycin, Levofloxacin and Ciprofloxacin, 80% sensitive to Nitrofurantoin and Teicoplanin, 60% sensitive to Vancomycin, Erythromycin and Cefixime and 20% sensitive to Cefotetan. The isolates were 100% resistant to cefradine and cloxacillin. So, for E. coli Azithromycin, Kanamycin and Ciprofloxacin were more sensitive and for Salmonella spp. Azithromycin, Kanamycin, Ciprofloxacin and Levofloxacin were highly sensitive. Diversified bacterial species were present in cloacal swabs of Turkeys. However, E. coli, Salmonella spp. infection might make the birds vulnerable for easy access of infection. It could be concluded that E. coli and Salmonella spp. may pass through the feces to the environment. It causes a potential human health hazards and can cause illness. Asian J. Med. Biol. Res. December 2017, 3(4): 419-425